Intersex child’s parents’ negative experiences – case study - Czerwiec, Karolina (Kultura-Społeczeństwo-Edukacja, 2022)
Intersexualism is often treated as a secret in medical and family systems. According to the thesis that intersex body is pathological and requires immediate surgical and hormonal regulation, intersex persons are subject to the process which involves rapid production of normative masculinity or femininity through invasive clinical practices. The goal of the study was to diagnose the experiences of parents of an intersex child with searching for support during the treatment for both the child and themselves. The study was conducted by means of individual semi-structured interview. The results are presented as a case study. It was shown that parents do not always receive the necessary social and medical support, and their children are treated as sensations and pathologies, regardless of the fact that empathy and acceptance are critical for making the right treatment-related decisions.